Long terminal repeat retrotransposons of Oryza sativa - McCarthy, Eugene M (BioMed Central, 2002)
BACKGROUND: Long terminal repeat (LTR) retrotransposons constitute a major fraction of the genomes of higher plants. For example, retrotransposons comprise more than 50% of the maize genome and more than 90% of the wheat genome. LTR retrotransposons are believed to have contributed significantly to the evolution of genome structure and function. The genome sequencing of selected experimental and agriculturally important species is providing an unprecedented opportunity to view the patterns of variation existing among the entire complement of retrotransposons in complete genomes. RESULTS: Using a new data-mining program, LTR_STRUC, (LTR retrotransposon structure program), we have mined the GenBank rice (Oryza sativa) database as well as the more extensive (259 Mb) Monsanto rice dataset for LTR retrotransposons. Almost two-thirds (37) of the 59 families identified consist of copia-like elements, but gypsy-like elements outnumber copia-like elements by a ratio of approximately 2:1. At least 17% of the rice genome consists of LTR retrotransposons. In addition to the ubiquitous gypsy- and copia-like classes of LTR retrotransposons, the rice genome contains at least two novel families of unusually small, non-coding (non-autonomous) LTR retrotransposons. CONCLUSIONS: Each of the major clades of rice LTR retrotransposons is more closely related to elements present in other species than to the other clades of rice elements, suggesting that horizontal transfer may have occurred over the evolutionary history of rice LTR retrotransposons. Like LTR retrotransposons in other species with relatively small genomes, many rice LTR retrotransposons are relatively young, indicating a high rate of turnover.